Situated Dialog in Speech-Based Human-Computer Interaction - Rudnicky, Alexander; Raux, Antoine; Lane, Ian.; Misu, Teruhisa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides a survey of the state-of-the-art in the practical implementation of Spoken Dialog Systems for applications in everyday settings. It includes contributions on key topics in situated dialog interaction from a number of leading researchers and offers a broad spectrum of perspectives on research and development in the area. In particular, it presents applications in robotics, knowledge access and communication and covers the following topics: dialog for interacting with robots; language understanding and generation; dialog architectures and modeling; core technologies; and the analysis of human discourse and interaction. The contributions are adapted and expanded contributions from the 2014 International Workshop on Spoken Dialog Systems (IWSDS 2014), where researchers and developers from industry and academia alike met to discuss and compare their implementation experiences, analyses and empirical findings.
Evaluation of Statistical POMDP-based Dialogue Systems in Noisy Environments -- Syntactic Filtering and Content-based Retrieval of Twitter Sentences for the Generation of System Utterances in Dialogue Systems -- Integrated Interpretation and Generation of Task-Oriented Dialog -- Justification and Transparency Explanations in Dialogue Systems to Maintain Human-Computer Trust -- Dialogue Management for User-centered Adaptive Dialogue -- Chat-like Conversational System based on Selection of Reply Generating Module with Reinforcement Learning -- Investigating Critical Speech Recognition Errors in Spoken Short Messages -- 8. The HRI-CMU Corpus of Situated In-Car Interactions -- Detecting 'Request Alternatives' User Dialog Acts from Dialog Context -- Emotion and Its Triggers in Human Spoken Dialogue: Recognition and Analysis -- Evaluation of In-Car SDS Notification Concepts for Incoming Proactive Events -- Construction and Analysis of a Persuasive Dialogue Corpus -- Evaluating Model that Predicts When People will Speak to a Humanoid Robot and Handling Variations of Individuals and Instructions -- Entrainment in Pedestrian Direction Giving: How many kinds of entrainment?.-Situated Interaction in a Multilingual Spoken Information Access Framework -- WFSTDM Builder - Network-based Spoken Dialogue System Builder for Easy Prototyping -- A demonstration of a natural-language pedestrian routing system -- Web-based Multimodal Multi-domain Spoken Dialogue System -- A Framework for Domain-specific Multi-modal Dialog System Creation -- A Trialogue-Based Spoken Dialogue System for Assessment of English Language Learners -- A Turbo-Decoding Weighted Forward-Backward Algorithm for Multimodal Speech Recognition -- Engine-independent ASR Error Management for Dialog Systems -- Restoring Incorrectly Segmented Keywords and Turn-Taking Caused by Short Pauses -- Investigating Critical Speech Recognition Errors in Spoken Short Messages -- A semi-automated evaluation metric for dialogue model coherence.
Keywords: Engineering; User interfaces (Computer systems).; Pattern recognition; Computational linguistics; Engineering; Signal, Image and Speech Processing; User Interfaces and Human Computer Interaction; Pattern Recognition; Computational Linguistics; Electronic books